2001
DOI: 10.1007/s004640080189
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic augmentation of the cardia with a biocompatible injectable polymer (Enteryx) in a porcine model

Abstract: Augmentation of the cardia with an injectable polymer (Enteryx) is simple, safe, and durable. Early studies suggest that alteration in the distensibility and geometry of the gastroesophageal junction may provide antireflux protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 16 publications
1
24
1
2
Order By: Relevance
“…If the material does not come into contact with the surrounding esophageal tissue, no tissue alteration should interfere with a surgical procedure. This was demonstrated in preclinical animal trials [3] and 1 69 12 36 16 22 36 --3 6 2 39 41 39 11 13 38 --3 5 3 35 11 21 10 1 0 0 21 12 28 4 7 2 1 0 2 3 3 9 2 7 2 7 1 7 6 2 4 Fig. 1.…”
Section: Discussionmentioning
confidence: 66%
“…If the material does not come into contact with the surrounding esophageal tissue, no tissue alteration should interfere with a surgical procedure. This was demonstrated in preclinical animal trials [3] and 1 69 12 36 16 22 36 --3 6 2 39 41 39 11 13 38 --3 5 3 35 11 21 10 1 0 0 21 12 28 4 7 2 1 0 2 3 3 9 2 7 2 7 1 7 6 2 4 Fig. 1.…”
Section: Discussionmentioning
confidence: 66%
“…The initial study for safety and efficacy of this material was done by Mason et al [55], who injected 12 Yucatan minipigs with Enteryx. Four groups of three animals each were killed at 2, 6, 12, and 24 weeks following implantation.…”
Section: Clinical Studies and Resultsmentioning
confidence: 99%
“…Animal studies suggested that implantation is safe and likely efficacious [15]. All animals tolerated the implants without alimentary difficulties or weight loss.…”
Section: Discussionmentioning
confidence: 98%